Evolution in Medicinal Chemistry of Ursolic Acid Derivatives as Anticancer Agents - Chen, Haijun (Eur J Med Chem, 2015)
Currently, there is a renewed interest in common dietaries and plant-based traditional medicines for the prevention and treatment of cancer. In the search for potential anticancer agents from natural sources, ursolic acid (UA), a pentacyclic triterpenoid widely found in various medicinal herbs and fruits, exhibits powerful biological effects including its attractive anticancer activity against various types of cancer cells. However, the limited solubility, rapid metabolism and poor bioavailability of UA restricted its further clinical applications. In the past decade, with substantial progress toward the development of new chemical entities for the treatment of cancer, numerous UA derivatives have been designed and prepared to overcome its disadvantages. Despite extensive effort, discovery of effective UA derivatives has so far met with only limited success. This review summarizes the current status of the structural diversity and evolution in medicinal chemistry of UA analogues and provides a detailed discussion of future direction for further research in the chemical modifications of UA.